A method for preparing a super-hydrophobic surface with excellent interfacial adhesion

CN122400115BActive Publication Date: 2026-10-23DALIAN UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610882368.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-06-18
Publication Date
2026-10-23
Estimated Expiration
2046-06-18

AI Technical Summary

Technical Problem

[0008]本发明针对现有技术中超疏水表面制备过程中,超疏水涂层与基底界面黏附力不足、易脱落、抗冷凝性差的技术缺陷,提供了一种优异界面黏附力超疏水表面的制备方法

Benefits of technology

(1)本发明的过渡层通过“化学键合+兼容性优化+结构互锁”的协同作用,有效地提升了超疏水涂层与基底之间的界面黏附力,解决了现有技术中涂层与基底之间由于物理结合而导致的易脱落、兼容性差等缺陷;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122400115B_ABST
    Figure CN122400115B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of functional surface material modification, and particularly relates to a preparation method of an excellent interfacial adhesion super-hydrophobic surface. The method comprises the following steps: (1) ultrasonic cleaning of a substrate; (2) adding fumed nano-silica into anhydrous ethanol and stirring on a magnetic stirrer, slowly adding an alkaline silicon solution during the stirring process, and continuously stirring to obtain a transition layer precursor solution; (3) spraying the transition layer precursor solution obtained in step (2) onto the substrate surface obtained in step (1), and forming a transition layer on the substrate surface by heating; and (4) using high-vacuum silicon grease as a super-hydrophobic coating material, and using a vapor deposition method or a spraying method to prepare a super-hydrophobic coating on the transition layer prepared in step (3), so as to obtain a super-hydrophobic surface. The transition layer of the present application effectively improves the interfacial adhesion between the super-hydrophobic coating and the substrate through the synergistic effect of "chemical bonding + compatibility optimization + structure interlocking".
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of functional surface material modification technology, and more particularly to a method for preparing a superhydrophobic surface with excellent interfacial adhesion. Background Technology

[0002] Superhydrophobic surfaces, with their core characteristics of droplet contact angles greater than 150° and roll-off angles less than 10°, have broad application prospects in fields such as anti-condensation, self-cleaning, corrosion prevention, anti-icing, and anti-fouling, especially in metal components used in high-humidity and low-temperature environments, where they hold an irreplaceable position. Aluminum and aluminum alloy products, with their advantages of light weight, good thermal conductivity, and ease of processing and forming, are widely used in refrigeration equipment accessories, outdoor aluminum building materials, and heat sinks for electronic devices. Superhydrophobic modification of their surfaces has become a major research hotspot in the field of metal surface modification in recent years. With the rapid development of science and technology, the preparation methods of aluminum-based superhydrophobic surfaces have formed a diversified development pattern. Common preparation methods include spraying, etching, and hydrothermal methods, and many of these methods have achieved breakthrough progress.

[0003] Among these methods, spraying has become one of the most promising technologies in industrial applications due to its simple equipment, convenient operation, and suitability for large-scale production. It rapidly constructs superhydrophobic surfaces by mixing and spraying hydrophobic particles with a binder. Etching and hydrothermal methods achieve superhydrophobicity by constructing micro-nano rough structures on the substrate surface, combined with low surface energy modification. However, in practical applications, when subjected to friction, scratching, fluid impact, or long-term water vapor erosion, the superhydrophobic coating is prone to peeling due to insufficient interfacial adhesion to the metal substrate, leading to a reduction or even loss of superhydrophobic function. This seriously affects the service life and reliability of aluminum components. This is not only a common problem of existing technologies but also a major reason why superhydrophobic coatings are currently difficult to widely apply in high-frequency friction and strong corrosion conditions such as aerospace components and marine equipment.

[0004] To address the aforementioned problem of insufficient interfacial adhesion, existing technologies have undergone a series of improvements and optimizations, but these have significant limitations and cannot fundamentally overcome the technical bottleneck. One type is physical modification methods, such as surface grinding and sandblasting. These methods increase the surface roughness of the metal substrate, thereby increasing the physical contact area between the coating and the substrate, and thus enhancing interfacial adhesion. However, this method easily damages the natural oxide layer on the aluminum substrate surface, leading to a decrease in the substrate's corrosion resistance, and it does not form stable chemical bonds, resulting in limited enhancement of interfacial adhesion; after repeated friction, the coating still peels off. Another optimization approach is chemical blending modification. This involves adding modifiers such as silane coupling agents, epoxy resins, and metal oxide particles as auxiliary agents to attempt to improve the interfacial adhesion between the coating and the metal substrate. However, these methods mostly only improve the internal bonding strength of the coating and are difficult to effectively improve the interfacial bonding state between the coating and the substrate. Silane coupling agents and epoxy resins can decompose or even carbonize under high-temperature firing, leading to the failure of superhydrophobicity. Furthermore, the addition of modifiers can complicate the process, increase costs, and cause some nanoparticles to agglomerate, resulting in a decrease in coating adhesion.

[0005] Secondly, existing technologies struggle to achieve a synergistic improvement in superhydrophobicity, anti-condensation properties, and interfacial adhesion. Most preparation methods, in pursuit of high hydrophobicity, excessively optimize the surface roughness structure, neglecting the impact of the structure on adhesion and anti-condensation performance. Either the roughness structure is too porous, leading to easy coating detachment; or the structural parameters are unreasonable, failing to achieve stable Cassie state of condensate droplets, causing condensation to easily adhere to the surface in high-humidity environments, thus losing its anti-condensation function. Simultaneously, some technologies use high-viscosity adhesives or excessively roughen the substrate to improve adhesion, which in turn damages the microstructure of the superhydrophobic surface, leading to a decrease in hydrophobicity.

[0006] Vapor deposition (CVD) can precisely construct layered micro / nano-scale rough structures at the atomic / molecular level, offering significant advantages such as uniform film thickness, strong adhesion, wide substrate versatility, no damage to the substrate, and excellent wear resistance and stability. Furthermore, CVD itself occurs at high temperatures, making it an ideal method for preparing high-performance, highly stable, industrially viable, and long-life superhydrophobic coatings. However, traditional CVD-prepared superhydrophobic coatings exhibit low interfacial adhesion to the substrate; even a gentle blow with dry gas can cause the superhydrophobic coating to detach, leading to coating failure.

[0007] Therefore, developing a preparation method that can significantly improve the adhesion between the superhydrophobic coating and the metal substrate while taking into account superhydrophobic properties, anti-condensation properties and excellent stability has become a technical challenge that urgently needs to be overcome. Summary of the Invention

[0008] This invention addresses the shortcomings of existing superhydrophobic surface preparation techniques, such as insufficient adhesion between the superhydrophobic coating and the substrate, easy detachment, and poor condensation resistance. It provides a method for preparing a superhydrophobic surface with excellent interfacial adhesion. The core of this invention lies in constructing a special transition layer to effectively enhance the interfacial adhesion between the superhydrophobic coating and the substrate, thereby improving the surface's thermal stability and achieving excellent condensation resistance. To achieve the above objectives, this invention is implemented through the following technical solution:

[0009] This invention provides a method for preparing a superhydrophobic surface, the method comprising the following steps: (1) Perform ultrasonic cleaning on the substrate; (2) Add fumed nano-silica to anhydrous ethanol and place it on a magnetic stirrer. During the stirring process, slowly add alkaline silicon solution and continue stirring to obtain the transition layer precursor solution. (3) Spray the transition layer precursor liquid obtained in step (2) onto the substrate surface obtained in step (1), and form a transition layer on the substrate surface by heating; (4) On the transition layer prepared in step (3), a superhydrophobic coating is prepared by using high vacuum silicone grease as the superhydrophobic coating material and by using vapor deposition or spraying method to obtain a superhydrophobic surface.

[0010] In the above technical solution, further, in step (1), the material of the substrate includes one of metal, ceramic, glass and stone.

[0011] In the above technical solution, further, in step (1), acetone, anhydrous ethanol and deionized water are used in sequence to ultrasonically clean the substrate to remove residual oil and impurities on the substrate.

[0012] In the above technical solution, further, in step (2), the particle size of the fumed nano silica is 7~500nm, and its surface has abundant hydroxyl groups, which can react with the active groups in the alkaline silicon solution.

[0013] In the above technical solution, further, in step (2), the alkaline silicon solution is one of methacryloyloxysilane, tetraethyl orthosilicate, alkylsilane, and epoxysilane. The main purpose of adding the alkaline silicon solution during the preparation of the fumed silica nano-suspension is to utilize the active silicon species in the alkaline silicon solution to chemically bond with the hydroxyl groups on the surface of the fumed silica nano-suspension and the hydroxyl groups on the substrate surface, while simultaneously adjusting the stability of the precursor solution and preventing the agglomeration of the fumed silica nano-suspension particles. The alkaline silicon solution is added at a rate of 2-3 drops / second; slow addition avoids excessively high local pH values ​​that could lead to agglomeration of the fumed silica nano-suspension, thereby ensuring the uniformity of the precursor solution.

[0014] In the above technical solution, further, in step (2), the stirring time of the whole process is 4~6 h and the stirring speed is 200~600 r / min.

[0015] In the above technical solution, further, in step (3), a spray gun is used for spraying. The nozzle diameter of the spray gun is 0.8 mm. It is connected to an air compressor, and compressed air is used as the carrier. The spray shape is adjusted to be straight. The spraying pressure is between 0.3 and 0.5 MPa. The distance between the nozzle and the substrate is maintained at 10 to 15 cm. The nozzle axis is at an angle of 30° to 50° with the normal direction of the substrate surface. Spraying is carried out from left to right at a speed of 8 to 12 cm / s. The spraying is repeated 50 to 70 times.

[0016] In the above technical solution, further, in step (3), during the process of spraying the transition layer precursor liquid, the substrate is heated in order to accelerate the evaporation of anhydrous ethanol and obtain a uniformly distributed transition layer. The heating temperature is 70~80 ℃.

[0017] In the above technical solution, further, in step (4), the specific steps of the vapor deposition method are as follows: apply high vacuum silicone grease evenly to the bottom of the container, invert the substrate with the transition layer coated on the surface onto the container, and heat it to 350 ℃ at a heating rate of 5~10℃ / min in an air atmosphere, and keep it at that temperature for 3 h. After the temperature drops below 200 ℃, take out the sample. The high vacuum silicone grease in the vapor deposition container needs to be applied evenly and smoothly, with a thickness of about 1 / 3 of the container height, to ensure that there is enough gas generated during the high-temperature decomposition process and that it can fully act on the transition layer on the substrate surface to achieve uniform deposition of the superhydrophobic coating on the substrate. The substrate needs to be placed in the middle of the container and should not completely cover the container, otherwise the deposited coating will not be evenly distributed on the substrate.

[0018] In the above technical solution, further, in step (4), the specific steps of the spraying method are as follows: mix high vacuum silicone grease and polydimethyl silicone oil, stir with a magnetic stirrer to dissolve the high vacuum silicone grease into the polydimethyl silicone oil to obtain a superhydrophobic coating precursor liquid, spray the superhydrophobic coating precursor liquid evenly onto the substrate surface coated with the transition layer, heat it from room temperature to 350 ℃ within 10 min in an air atmosphere, keep it at the temperature for 2.5 h for heat treatment, and then cool it naturally to room temperature.

[0019] In the above technical solution, further, in the superhydrophobic coating precursor liquid, the mass-to-volume ratio of high-vacuum silicone grease and polydimethyl silicone oil is 0.3 g: 10 mL, the viscosity of polydimethyl silicone oil is 10 cSt, the mixing time of the mixed solution is 1~3 h, and the stirring speed is 300~600 r / min. Polydimethyl silicone oil acts as a solvent to dissolve the high-vacuum silicone grease in the paste. Using low-viscosity polydimethyl silicone oil can avoid clogging the spray gun nozzle. It can also be replaced by one or more of chlorinated solvents, aromatic hydrocarbon solvents, and silicone-based solvents.

[0020] In the above technical solution, a spray gun is further used for spraying. During the spraying process, the nozzle diameter of the spray gun is 0.8 mm. It is connected to an air compressor, uses compressed air as a carrier, adjusts the spray shape to a fan shape, and the spraying pressure is between 0.35 and 0.6 MPa. The distance between the nozzle and the substrate is maintained at 10 to 15 cm. The nozzle is perpendicular to the substrate surface and at an angle of 30° to 50° with the horizontal plane. The spraying is carried out from left to right at a speed of 8 cm / s, and the spraying is repeated 20 to 40 times.

[0021] In the above technical solution, further, in step (4), during heat treatment, a multi-layer metal frame can be used to separate multiple substrates for heating, thereby maximizing space utilization and effectively reducing processing costs.

[0022] The beneficial effects of this invention are as follows: (1) The transition layer of the present invention effectively improves the interfacial adhesion between the superhydrophobic coating and the substrate through the synergistic effect of "chemical bonding + compatibility optimization + structural interlocking", which solves the defects of easy peeling and poor compatibility caused by physical bonding between the coating and the substrate in the prior art. (2) The final prepared hydrophobic surface has a water contact angle ≥163° and a roll-off angle ≤2°, exhibiting excellent superhydrophobic properties. After dozens of cycles of steam at 100 ℃ and freezing at approximately -10 ℃, the superhydrophobic coating on the substrate surface not only did not peel off, but its superhydrophobic properties also remained intact. Under supercooled and high-humidity conditions, condensate droplets on the surface of the superhydrophobic coating can spontaneously detach, with most droplets ranging from 50 to 100 μm in size. Only a very small number of droplets have larger detachment sizes. This is because the multi-level micro-nano rough structure of the surface can effectively inhibit the formation and adhesion of condensate, resulting in a significant anti-condensation effect.

[0023] (3) The method of the present invention does not require complicated equipment and reagents. A transition layer is prepared on the substrate surface by spraying process. The preparation process is simple and can be prepared on a large area. Furthermore, a superhydrophobic coating is prepared by vapor deposition or spraying process. The superhydrophobic coatings prepared by both methods have excellent superhydrophobic properties and anti-condensation properties. Moreover, the materials used in the preparation process are inexpensive and readily available. (4) The results of tape peeling test and friction test show that the superhydrophobic coating containing the transition layer did not peel off or break from the aluminum substrate surface; while the superhydrophobic coating without the transition layer will quickly peel off from the aluminum substrate surface and lose its superhydrophobicity. The experimental comparison proves that the transition layer prepared by the present invention can effectively improve the interfacial adhesion between the superhydrophobic coating and the substrate, and achieve the long-term stability of the superhydrophobic coating. Attached Figure Description

[0024] Figure 1 Optical images and surface characterization diagrams of the transition layer and superhydrophobic surface sample prepared in Example 1 are shown. (a) is an optical image and scanning electron microscope image of the transition layer, (b) is an optical image and scanning electron microscope image of the superhydrophobic surface sample, and (c) is a surface contact angle measurement diagram of the superhydrophobic surface sample. Figure 2 The images shown are hyper-depth images before and after tape peeling in Examples 1 and Comparative Examples 1 and 2, and graphs showing the changes in contact angle and roll-off angle with the number of tape peeling cycles. (a) is the hyper-depth image before tape peeling in Example 1, (b) is the hyper-depth image after tape peeling in Example 1, (c) is the graph showing the changes in contact angle and roll-off angle with the number of tape peeling cycles in Example 1, (d) is the hyper-depth image before tape peeling in Comparative Example 1, (e) is the hyper-depth image after tape peeling in Comparative Example 1, (f) is the graph showing the changes in contact angle and roll-off angle with the number of tape peeling cycles in Comparative Example 1, (g) is the hyper-depth image before tape peeling in Comparative Example 2, (h) is the hyper-depth image after tape peeling in Comparative Example 2, and (i) is the graph showing the changes in contact angle and roll-off angle with the number of tape peeling cycles in Comparative Example 2. Figure 3 The images shown are optical images and results of the wear test on the superhydrophobic surface sample of Example 1. (a) is a test process diagram, and (b) is an experimental result diagram. Figure 4 The images show the freezing-defrosting optical images and results of the superhydrophobic surface samples of Example 1 and Comparative Example 2. (a) shows the second freezing-defrosting of the Comparative Example 2 sample, (b) shows the fortieth freezing-defrosting of the Comparative Example 2 sample, (c) shows the second freezing-defrosting of the Example 1 sample, and (d) shows the fortieth freezing-defrosting of the Example 1 sample. Figure 5 The following are experimental images of the anti-condensation performance of the superhydrophobic surface sample in Example 1: (a) shows the microscopic state, and (b) shows the experimental results. Figure 6 The test results of the superhydrophobic surface sample prepared in Example 2 are shown in (a) and (b) respectively. (c) is the super depth-of-field image before tape peeling, (d) is the super depth-of-field image after tape peeling, (c) is the graph showing the change of contact angle and roll-off angle with the number of tape peelings, and (d) is the graph showing the change of contact angle and roll-off angle with the heating time of hot steam. Detailed Implementation

[0025] The following examples are intended to enable those skilled in the art to more fully understand the present invention, but do not limit the invention in any way.

[0026] Unless otherwise specified, the materials used in the embodiments of the present invention can be obtained commercially or prepared according to conventional methods known to those skilled in the art.

[0027] Comparative Example 1 Preparation method of commercial superhydrophobic surface samples: A 76×26×1 mm aluminum sheet was selected as the substrate material. It was ultrasonically cleaned for 3 min in sequence with acetone, anhydrous ethanol and deionized water to remove oil and impurities remaining on the surface of the aluminum sheet. The cleaned aluminum sheet was dried in a vacuum drying oven. Then, a commercial superhydrophobic coating (purchased from RPM Company, USA) was sprayed onto the aluminum sheet and dried in a vacuum drying oven at 70 °C for 30 min to obtain a commercial superhydrophobic surface.

[0028] Comparative Example 2 Preparation of superhydrophobic surface samples without a transition layer: (1) Pretreatment of aluminum sheet substrate: 76×26×1 mm aluminum sheet is selected as substrate material. Acetone, anhydrous ethanol and deionized water are used to ultrasonically clean it for about 3 minutes to remove oil and impurities remaining on the surface of the aluminum sheet. The cleaned aluminum sheet is dried in a vacuum drying oven and placed on the spraying platform for later use. (2) Vapor deposition of superhydrophobic coating: Weigh 4 g of high vacuum silicone grease using a precision balance, apply the high vacuum silicone grease evenly to the bottom of the corundum crucible using a glass rod, place the aluminum sheet upside down on top of the corundum crucible and place it in a box-type resistance furnace, set the deposition temperature to 350 ℃ and the deposition time to 3 h for high-temperature vapor deposition, and take it out after the temperature in the box-type resistance furnace drops below 200 ℃, use dry gas to blow away excess deposited particles on the surface to obtain a superhydrophobic surface sample.

[0029] Example 1 A method for preparing superhydrophobic surfaces using vapor phase deposition includes the following steps: (1) Pretreatment of aluminum sheet substrate: In this embodiment, an aluminum sheet of 76×26×1 mm is selected as the substrate material. Acetone, anhydrous ethanol and deionized water are used to ultrasonically clean it for about 3 minutes to remove the oil and impurities remaining on the surface of the aluminum sheet. The cleaned aluminum sheet is dried in a vacuum drying oven and placed on the spraying platform for later use. (2) Preparation of transition layer precursor solution: Weigh 0.5 g of fumed nano silica with a particle size of 7~40 nm, add 40 mL of anhydrous ethanol, place the mixture on a magnetic stirrer and stir. During the stirring process, slowly add 3 mL of alkaline silicon solution at a rate of 2~3 drops / second, and continue stirring for 5 h at a stirring speed of 400 r / min to obtain a stable transition layer precursor solution. (3) Spraying of transition layer: The transition layer precursor liquid obtained in step (2) is sprayed onto the surface of the pretreated aluminum sheet through a 0.8 mm diameter pot spray gun of type R51-F. During the spraying process, the air pressure is set to 0.4 MPa, the spraying flow rate is 80 mL / min, the distance between the spray gun nozzle and the substrate is 10 cm, the nozzle axis is at 45° with the normal direction of the substrate surface, and it moves from left to right at a speed of 10 cm / s. The spraying is repeated about 60 times. During the spraying process, the aluminum sheet can be placed on a heating platform of 70~80 ℃ to accelerate the evaporation of anhydrous ethanol and form a uniform transition layer on the surface of the aluminum sheet. (4) Preparation of superhydrophobic coating by vapor deposition: Weigh 4 g of high vacuum silicone grease using a precision balance, and use a glass rod to evenly spread the high vacuum silicone grease on the bottom of the corundum crucible. Place the aluminum sheet coated with the transition layer upside down on top of the corundum crucible and place it in a box-type resistance furnace. Set the deposition temperature to 350 ℃ and the deposition time to 3 h for high-temperature vapor deposition. After the temperature in the box-type resistance furnace drops below 200 ℃, take it out and use dry gas to blow away the excess deposited particles on the surface to obtain a superhydrophobic surface sample.

[0030] Performance tests were conducted on the samples from Example 1, Comparative Example 1, and Comparative Example 2: 1. The surface morphology of the transition layer and the superhydrophobic coating prepared in Example 1, as well as the superhydrophobicity of the superhydrophobic coating, were tested: Macroscopic images of the transition layer were recorded using an optical camera, and the surface morphology of the coating was characterized using a scanning electron microscope. The microporous and rough structure of the transition layer surface can increase the contact area with the subsequent superhydrophobic coating, such as... Figure 1 As shown in (a), a superhydrophobic coating was deposited on the surface of the transition layer by vapor deposition. Scanning electron microscopy revealed an uneven, micro / nano-scale cauliflower-like structure on the surface of the superhydrophobic coating, as shown in (a). Figure 1 As shown in (b).

[0031] The high-vacuum silicone grease decomposes under high heat and continuously deposits on the aluminum sheet surface, forming a micro-nano-scale structure that provides the conditions for superhydrophobic properties. The contact angle of the coating was measured using a TBU 100 contact angle meter with a water droplet size of 3 μL. Five points were selected for measurement on each sample, and the average value was taken. Figure 1(c) shows the roll-off angle of the sample surface. The roll-off angle was measured using the inclined plate method: Before measurement, the sample stage was leveled. 3 μL of deionized water was pipetted onto the sample surface, and the tilt angle of the sample stage was slowly rotated until the water droplet began to move and slide off. The angle rotated at this point was recorded as the roll-off angle. At least five points were selected for measurement for each sample, and the average value was taken. All measurements were performed at room temperature. The measured contact angle of the sample surface was 163°, and the roll-off angle was 2°.

[0032] 2. The interfacial adhesion between the superhydrophobic coating and the aluminum substrate was tested: The superhydrophobic coating sample with a transition layer from Example 1, the commercial superhydrophobic coating from Comparative Example 1, and the superhydrophobic sample without a transition layer from Comparative Example 2 were placed on a platform with sufficient hardness. Holding the handle of a scribing tool with the blade perpendicular to the platform surface, a cross pattern was drawn on the surface of the samples using uniform pressure and a steady speed (20 mm / s) to form a grid pattern. Debris was cleaned from the surface of the samples using a soft brush. Adhesive tape was then firmly applied to the grid pattern, and pressure was applied with fingers. After the tape was firmly attached, it was peeled off the surface at a uniform speed. The residual superhydrophobic coating on the surface of the samples was observed, and the contact angle and roll-off angle at the location were tested. The interfacial adhesion between the superhydrophobic coating and the aluminum substrate before and after peeling was compared. Figure 2 As shown in the figure. After 12 tape peels, the cut edges of the sample remained smooth, with no peeling observed. The interfacial adhesion strength met the 5B standard. The contact angle and roll-off angle of the superhydrophobic surface remained at 159° and 7°, respectively. The experimental results demonstrate that the sample possesses good mechanical stability. Figure 2 (a) ~ Figure 2 As shown in (c), the superhydrophobic coating on the surface of Comparative Example 1 peels off significantly with increasing tape peeling cycles, but its superhydrophobic properties do not decrease significantly. Figure 2 (d)~ Figure 2 As shown in (f). In fact, the superhydrophobic coating on the surface of Comparative Example 2 showed extensive peeling off during the first tape peeling. With each tape peeling, the exposed area of ​​the underlying aluminum substrate increased, the superhydrophobicity decreased significantly, and the roll-off angle increased markedly. By the 12th tape peeling, the superhydrophobic coating of Comparative Example 2 had completely detached from the aluminum substrate, as shown in (f). Figure 2 (g)~ Figure 2 As shown in (i).

[0033] 3. The wear resistance of the sample obtained in Example 1 was tested: Place the sample upside down on 800-grit sandpaper, ensuring the coated surface is in contact with the sandpaper. Place a 50 g weight on the sample. Use tweezers to push the sample along a ruler, moving it 10 cm. Then, push the sample back to the starting point from the other side in the opposite direction. This process is defined as one friction cycle. Figure 3 As shown in (a), the surface wettability change was recorded every 10 friction cycles. The results show that after 60 friction cycles, the sample coated with the transition layer still exhibits stable superhydrophobic properties, as shown in the experimental results. Figure 3 As shown in (b).

[0034] 4. The superhydrophobic properties of the samples prepared in Example 1 and Comparative Example 2 were tested under extreme environments. A support was set up on a water bath (HH-WO-2L, Yuhua Instruments, China). After the water boiled, the samples from Example 1 and Comparative Example 2 were inverted and placed on the support, allowing the hot steam to fully contact the surfaces for about 1 minute. Then, both samples were placed in a sub-zero temperature environment to freeze for 10 minutes. They were then removed and placed back on the support for defrosting with hot steam. This process was counted as one cycle, and a total of 40 cycles were performed. Figure 4 (a) ~ Figure 4 As shown in (b), the superhydrophobic coating on the surface of Comparative Example 2 showed significant peeling during the second cycle, and lost its original superhydrophobic properties after 40 cycles. In contrast, the superhydrophobic coating of Example 1 showed no significant change after 40 freeze-defrost cycles, retaining stable superhydrophobicity. Figure 4 (c)~ Figure 4 As shown in (d). Through comparison of experimental results, it can be demonstrated that the transition layer of the present invention can not only effectively enhance the interfacial adhesion between the superhydrophobic coating and the metal substrate, but also improve the mechanical and thermal stability of the superhydrophobic coating.

[0035] 5. The anti-condensation properties of the sample prepared in Example 1 were tested. A self-built condensation system was used for experiments, mainly consisting of a digital microscope system (VHX-S90F, Keyence, Japan), a cooling stage, and a humidifier (MTD3-M / K-02, Midea, China). The sample to be tested was attached to the cooling stage using thermally conductive silicone grease, which was then placed vertically on the moving stage of the digital microscope system. A layer of plastic wrap was placed over the inner surface of the PMMA chamber to create a stable humidity environment. The humidifier continuously humidified the chamber, maintaining a humidity of approximately 90%, a temperature of ~15.3 ℃, and an ambient dew point of 13.9. The cooling stage temperature was set to 4 ℃ to maintain a supercooling of 10 ℃ on the sample surface. Condensation began when the sample surface temperature fell below the ambient dew point. The microscopic state of the condensate droplets on the sample surface was photographed using the digital microscope system. Figure 5As shown in (a). The diameter and coverage of the condensate droplets were calculated using ImageJ software, as shown. Figure 5 As shown in (b).

[0036] 6. Principle analysis of interfacial adhesion force in the transition layer: The core innovation of this invention lies in the preparation process of the transition layer. This transition layer acts as a "connecting bridge" between the aluminum substrate and the superhydrophobic coating, which can significantly improve the interfacial adhesion between the two. Its working principle is as follows: (1) Chemical bonding: The surface of the fumed silica nanoparticles in the transition layer contains a large number of Si-OH groups, and the active silicon species in the alkaline silicon solution (such as SiO3) 2- The Al-OH groups on the aluminum sheet surface can undergo condensation reactions with these Si-OH groups to form stable Si-O-Si covalent bonds. Simultaneously, the Al-OH groups on the aluminum sheet surface can also chemically react with the Si-OH groups in the transition layer to form Al-O-Si covalent bonds. The superhydrophobic coating formed by the deposition of vapor-phase silicon-based materials from the high-temperature decomposition of high-vacuum silicone grease is essentially a silicon-based system. The transition layer itself is also a silicon-based system, and the residual Si-OH groups on its surface can undergo condensation reactions with the active groups in the vapor-phase silicon-based materials to form Si-O-Si covalent bonds. This chemical bonding replaces the physical adsorption (van der Waals forces) between the coating and the substrate in existing technologies, significantly improving interfacial adhesion and thus solving the problem of easy coating detachment. (2) Improved interface compatibility: The transition layer is a silicon-based inorganic system. One end is tightly bonded to the aluminum base through Al-O-Si bonding, and the other end is compatible with the silicon-based superhydrophobic layer through Si-O-Si bonding, forming a "aluminum-silicon-based transition layer-silicon-based superhydrophobic layer" bonding system, reducing the risk of interface peeling; at the same time, the microporous structure of the transition layer can increase the contact area with the superhydrophobic coating, further enhancing the interface adhesion. (3) Synergistic enhancement effect: The fumed silica in the transition layer can construct a micro-rough structure. The superhydrophobic layer prepared subsequently forms a multi-level micro-nano rough structure of "nanoparticle-coating" on the primary rough structure, which further enhances the bonding strength between the coating and the substrate through structural interlocking.

[0037] Example 2 A method for preparing superhydrophobic surfaces using a spraying method includes the following steps: (1) Pretreatment of aluminum sheet substrate: In this embodiment, an aluminum sheet of 76×26×1 mm is selected as the substrate material. Acetone, anhydrous ethanol and deionized water are used to ultrasonically clean it for about 3 minutes to remove the oil and impurities remaining on the surface of the aluminum sheet. The cleaned aluminum sheet is dried in a vacuum drying oven and placed on the spraying platform for later use. (2) Preparation of transition layer precursor solution: Weigh 0.5 g of fumed nano silica with a particle size of 7~40 nm, add 40 mL of anhydrous ethanol, place the mixture on a magnetic stirrer and stir. During the stirring process, slowly add 3 mL of alkaline silicon solution at a rate of 2~3 drops / second, and continue stirring for 5 h at a stirring speed of 400 r / min to obtain a stable transition layer precursor solution. (3) Spraying of transition layer: The above-mentioned transition layer precursor liquid is sprayed onto the surface of the pretreated aluminum sheet through a 0.8 mm diameter pot spray gun of type R51-F. During the spraying process, the air pressure is set to 0.4 MPa, the spraying flow rate is 80 mL / min, the distance between the spray gun nozzle and the substrate is 10 cm, the nozzle axis is at a 45° angle to the normal direction of the substrate surface, and it moves from left to right at a speed of 10 cm / s. The spraying is repeated about 60 times. During the spraying, it can be placed on a heating platform of 70~80 ℃ to accelerate the evaporation of anhydrous ethanol and form a uniform transition layer on the surface of the aluminum sheet. (4) Preparation of superhydrophobic coating precursor liquid: Weigh 0.3 g of high vacuum silicone grease using a precision balance, and weigh 10 mL of polydimethyl silicone oil with a viscosity of 10 cSt. Stir at a rate of 300 r / min for 2 h using a magnetic stirrer until the high vacuum silicone grease is completely dissolved to obtain a uniform superhydrophobic coating precursor liquid. (5) Spraying the superhydrophobic coating: The superhydrophobic coating precursor liquid was sprayed onto the surface of the aluminum substrate with the transition layer using a 0.8 mm nozzle top-pot spray gun of type R51-F. During the spraying process, the air pressure was set to 0.5 MPa, the spraying flow rate was 5 mL / min, the nozzle of the spray gun was 10 cm away from the substrate, and perpendicular to the substrate surface. Throughout the process, the spray gun moved from left to right at a speed of 8 cm / s, spraying about 30 times. The substrate coated with the transition layer and the superhydrophobic coating was placed in a box-type resistance furnace and heated from room temperature to 350 °C within 10 min in an air atmosphere, held at that temperature for 2.5 h, and then naturally cooled to room temperature to obtain the superhydrophobic surface sample.

[0038] Example 2 shows a superhydrophobic surface sample obtained using a spray coating process, exhibiting excellent superhydrophobicity (contact angle 175.5°, roll-off angle 2°). Even after 200 tape peels, the sample's cut edges remained smooth, with no peeling observed. The interfacial adhesion strength met the 5B standard, and the contact angle and roll-off angle of the superhydrophobic surface remained at 167.5° and 5°, respectively. The experimental results are as follows... Figure 6 (a) ~ Figure 6As shown in (c), the sample exhibits good mechanical stability. A support was installed on a water bath (HH-WO-2L, Yuhua Instruments, China). After the water boiled, the sample was inverted onto the support to ensure full contact between the surface and the hot steam. The surface wettability change of the sample was measured and recorded every 20 minutes using a contact angle meter. The results are shown in (c). Figure 6 As shown in (d), the coating surface still exhibits stable superhydrophobicity after a 3-hour hot steam condensation experiment. Even under extreme conditions, the superhydrophobic coating prepared by spraying retains stable superhydrophobicity and does not detach from the substrate surface.

[0039] Experiments have shown that the transition layer prepared by this invention can effectively enhance the interfacial adhesion between the superhydrophobic coating and the substrate, and the superhydrophobic coating prepared by either vapor deposition or spraying processes exhibits excellent stability.

[0040] Example 3 (1) Pretreatment of alumina ceramic substrate: In this embodiment, alumina ceramic sheet of 76×25×0.63 mm is selected as the substrate material. The ceramic sheet is ultrasonically cleaned for 3 min in sequence with acetone, anhydrous ethanol and deionized water to remove impurities remaining on the ceramic substrate. The cleaned ceramic sheet is placed in a vacuum drying oven to dry, and the clean ceramic sheet is placed on the spraying platform for later use. (2) Preparation of transition layer precursor solution: Weigh 0.5 g of fumed nano silica with a particle size of 7~40 nm, add 40 mL of anhydrous ethanol, place the mixture on a magnetic stirrer and stir. During the stirring process, slowly add 3 mL of alkaline silicon solution at a rate of 2~3 drops / second, and continue stirring for 5 h at a stirring speed of 400 r / min to obtain a stable transition layer precursor solution. (3) Spraying of transition layer: The above-mentioned transition layer precursor liquid is sprayed onto the surface of the pretreated ceramic sheet through a 0.8 mm diameter pot spray gun of type R51-F. During the spraying process, the air pressure is set to 0.4 MPa, the spraying flow rate is 80 mL / min, the distance between the spray gun nozzle and the substrate is 10 cm, the nozzle axis is at a 45° angle to the normal direction of the substrate surface, and it moves from left to right at a speed of 10 cm / s. The spraying is repeated about 60 times. During the spraying, it can be placed on a heating platform of 70~80 ℃ to accelerate the evaporation of anhydrous ethanol and form a uniform transition layer on the surface of the ceramic sheet. (4) Vapor-phase deposition of superhydrophobic coating: 4 g of high-vacuum silicone grease was weighed using a precision balance and evenly spread on the bottom of the corundum crucible using a glass rod. A ceramic sheet coated with a transition layer was placed upside down on top of the corundum crucible, and the crucible was placed in a box-type resistance furnace. The deposition temperature was set to 350 ℃ and the deposition time was 3 h for high-temperature vapor-phase deposition. After the temperature inside the box-type resistance furnace dropped below 200 ℃, the crucible was removed and excess deposited particles on the surface were blown away with dry gas to obtain a superhydrophobic surface sample. The contact angle of the sample surface was as high as 162.4° and the roll-off angle was as low as 2°. After multiple wear and peel resistance tests, the contact angle of the superhydrophobic surface remained at 154°.

[0041] Example 4 (1) Pretreatment of glass substrate: In this embodiment, a glass substrate of 76×26×1 mm is selected as the substrate material. The glass substrate is ultrasonically cleaned for 3 min in sequence with acetone, anhydrous ethanol and deionized water to remove impurities remaining on the glass substrate. The cleaned glass substrate is placed in a vacuum drying oven to dry, and the cleaned glass substrate is placed on the spraying platform for later use. (2) Preparation of transition layer precursor solution: Weigh 0.5 g of fumed nano silica with a particle size of 7~40 nm, add 40 mL of anhydrous ethanol, place the mixture on a magnetic stirrer and stir. During the stirring process, slowly add 3 mL of alkaline silicon solution at a rate of 2~3 drops / second, and continue stirring for 5 h at a stirring speed of 400 r / min to obtain a stable transition layer precursor solution. (3) Spraying of the transition layer: The above-mentioned transition layer precursor liquid is sprayed onto the surface of the pretreated glass slide through a 0.8 mm diameter pot spray gun of type R51-F. During the spraying process, the air pressure is set to 0.4 MPa, the spraying flow rate is 80 mL / min, the distance between the spray gun nozzle and the substrate is 10 cm, the nozzle axis is at a 45° angle to the normal direction of the substrate surface, and it moves from left to right at a speed of 10 cm / s. The spraying is repeated about 60 times. During the spraying, it can be placed on a heating platform of 70~80 ℃ to accelerate the evaporation of anhydrous ethanol and form a uniform transition layer on the surface of the glass slide. (4) Preparation of superhydrophobic coating precursor liquid: Weigh 0.3 g of high vacuum silicone grease using a precision balance, and weigh 10 mL of polydimethyl silicone oil with a viscosity of 10 cSt. Stir at a rate of 300 r / min for 2 h using a magnetic stirrer until the high vacuum silicone grease is completely dissolved to obtain a uniform superhydrophobic coating precursor liquid. (5) Spraying the superhydrophobic coating: The superhydrophobic coating precursor liquid was sprayed onto the surface of the glass substrate with the transition layer using a 0.8 mm nozzle top-pot spray gun of type R51-F. During the spraying process, the air pressure was set to 0.5 MPa, the spray flow rate was 5 mL / min, the nozzle of the spray gun was 10 cm away from the substrate, and perpendicular to the substrate surface. Throughout the process, the spray gun moved from left to right at a speed of 8 cm / s, spraying about 30 times. The substrate coated with the transition layer and the superhydrophobic coating was placed in a box-type resistance furnace and heated from room temperature to 350 °C within 10 min in an air atmosphere, held at that temperature for 2.5 h, and then naturally cooled to room temperature to obtain the superhydrophobic surface sample.

[0042] The superhydrophobic coating prepared on the glass substrate exhibits excellent superhydrophobicity (contact angle ~173.3°, roll-off angle ~2°). Furthermore, since both the glass, the transition layer, and the high-vacuum silicone grease contain SiO2, the superhydrophobic coating prepared by the spraying method exhibits excellent interfacial adhesion to the glass substrate.

[0043] The above-described embodiments are merely illustrative of the implementation methods of the present invention, but should not be construed as limiting the scope of the present invention. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these modifications and improvements all fall within the protection scope of the present invention.

Claims

1. A method for preparing a superhydrophobic surface, characterized in that, The method includes the following steps: (1) Perform ultrasonic cleaning on the substrate; (2) Add fumed nano-silica to anhydrous ethanol and place it on a magnetic stirrer. During the stirring process, slowly add alkaline silicon solution and continue stirring to obtain the transition layer precursor solution. (3) Spray the transition layer precursor liquid obtained in step (2) onto the substrate surface obtained in step (1), and form a transition layer on the substrate surface by heating; (4) On the transition layer prepared in step (3), a superhydrophobic coating is prepared by using high vacuum silicone grease as the superhydrophobic coating material and by using vapor deposition or spraying method to obtain a superhydrophobic surface. In step (1), the material of the substrate includes one of metal, ceramic, glass, and stone; In step (2), the alkaline silicon solution is one of methacryloxysilane, tetraethyl orthosilicate, alkylsilane, and epoxysilane, and the rate at which the alkaline silicon solution is added is 2-3 drops / second; In step (3), the heating temperature is 70~80 ℃.

2. The method for preparing a superhydrophobic surface according to claim 1, characterized in that, In step (1), the substrate is ultrasonically cleaned in sequence with acetone, anhydrous ethanol and deionized water.

3. The method for preparing a superhydrophobic surface according to claim 1, characterized in that, In step (2), the particle size of the vapor-phase nano-silica is 7~500 nm.

4. The method for preparing a superhydrophobic surface according to claim 1, characterized in that, In step (2), the stirring time for the entire process is 4~6 h, and the stirring speed is 200~600 r / min.

5. The method for preparing a superhydrophobic surface according to claim 1, characterized in that, In step (3), a spray gun is used for spraying. The nozzle diameter of the spray gun is 0.8 mm. It is connected to an air compressor and uses compressed air as a carrier. The spray shape is adjusted to be straight. The spraying pressure is 0.3~0.5 MPa. The distance between the nozzle and the substrate is kept at 10~15 cm. The nozzle axis is at an angle of 30°~50° to the normal direction of the substrate surface. Spraying is carried out from left to right at a speed of 8~12 cm / s. The spraying is repeated 50~70 times.

6. The method for preparing a superhydrophobic surface according to claim 1, characterized in that, In step (4), the specific steps of the vapor deposition method are as follows: apply high vacuum silicone grease evenly to the bottom of the container, invert the substrate with the transition layer coated on the surface onto the container, heat it to 350 ℃ at a heating rate of 5~10 ℃ / min in an air atmosphere, keep it at the temperature for 3 h, and take out the sample after the temperature drops below 200 ℃.

7. The method for preparing a superhydrophobic surface according to claim 1, characterized in that, In step (4), the specific steps of the spraying method are as follows: mix high vacuum silicone grease and polydimethyl silicone oil, stir with a magnetic stirrer to dissolve the high vacuum silicone grease into the polydimethyl silicone oil to obtain a superhydrophobic coating precursor liquid, spray the superhydrophobic coating precursor liquid evenly onto the substrate surface coated with the transition layer, heat it from room temperature to 350 ℃ within 10 min in an air atmosphere, keep it at the temperature for 2.5 h for heat treatment, and then cool it naturally to room temperature.

8. The method for preparing a superhydrophobic surface according to claim 7, characterized in that, In the superhydrophobic coating precursor solution, the mass-to-volume ratio of high-vacuum silicone grease and polydimethyl silicone oil is 0.3 g: 10 mL, the viscosity of polydimethyl silicone oil is 10 cSt, the mixing time of the mixed solution is 1~3 h, and the stirring speed is 300~600 r / min.

9. The method for preparing a superhydrophobic surface according to claim 7, characterized in that, Use a spray gun for spraying. During the spraying process, the nozzle diameter of the spray gun is 0.8 mm. Connect it to an air compressor and use compressed air as the carrier. Adjust the spray shape to a fan shape. The spraying pressure is between 0.35 and 0.6 MPa. Keep the distance between the nozzle and the substrate at 10 to 15 cm. The nozzle should be perpendicular to the substrate surface and at an angle of 30° to 50° to the horizontal plane. Spray from left to right at a speed of 8 cm / s. Repeat the spraying 20 to 40 times.

Citation Information

Patent Citations

  • Transparent super-hydrophobic coating material and method for preparing transparent super-hydrophobic coating by transparent super-hydrophobic coating material

    CN104449357A

  • Transparent antifouling coating material used for glass, and transparent antifouling coating and preparation method thereof

    CN105152546A